(untitled) (Al-Academy, 2024)
Filled the place thought philosophers and ancient is the identity that you know The value of belonging to a World Geography existential - the spiritual , and Which is characterized by the structure humanity from one another and the Rest of the organisms they interact with him alone by environmental Conditions - surrounding has to achieve time through continuous movement Localized or comprehensive . The place is exemplified by making special Natural Great Creator, I believe making structure humanity combined - Individual interactive because of its influential role in all daily consumer Productions and creative arts, specifically drama’s TV , because the place in Aesthetic discourse - TV drama directly affect the creating and building the Event by the moving image . Search came in four chapters , the first chapter The research problem and its importance and the need for and objectives and Its borders and its terminology and stand on her statement. Chapter II Consisted three Detectives first philosophy and concept of place , second Place in the novel and the story - the narrative place, third place in the TV drama , then indicators theoretical framework , and the third Contained a search procedures are represented in the sample and the Methodology of the analysis, and the fourth to discuss the results , and then the list of sources